The interface between TRIPS and CBD: efforts towards harmonisation - Laxman, Lekha; Ansari, Abdul Haseeb (Emerald Group Publishing, 2012)

(untitled)
Purpose – The purpose of this paper is to analyse the interface between the Trade Related Aspects of Intellectual Property Rights Agreement (TRIPS) and the Convention on Biological Diversity (CBD), to determine measures available to the global community to resolve the conflict between them, in order to prevent the rapid loss of biodiversity despite the diverse interests of nations.